Examination of the Effects of the Physical Properties of Woven Fabrics on the Heating of Sewing Machine Needles - (:unkn) unknown (INST CHEMICAL FIBRES, 2014)
The elementary process of the garment production process is sewing. Sewing, the most important element determining quality and durability in garment production, is the process of getting the sewing thread through the material that will be sewn with the help of a needle, either for the purpose of strengthening or trimming. This process is the backbone of the course of production. Carrying it out as desired will have an effect on utilising production resources and time spent in production more effectively and on achieving the quality level in the final product expected The heat generated as a result of the needle's friction against the surface of the textile and the properties of the fabric that affect the heating in the sewing process of woven fabrics were examined in this study Fabrics of seven different weights, densities and blends were used. An Optris CT3M Pyrometer was used in the implementation to measure the heat on the needle.
Keywords: sewing machine needle; heating; woven fabric